A cross-cultural comparison of music education experiences and ambitions in two Spanish and English primary schools. (August 2017) - Hardcastle, Elinor; Pitts, Stephanie; Aróstegui, José Luis
A small-scale comparative study of music education provision in two Spanish and English primary schools was carried out in 2013–14, using questionnaires, interviews and observations. The study investigated the musical experiences of the children in the two schools, their ambitions for their musical futures, and the classroom practices and policy contexts that shaped these encounters with musical learning. Through thematic analysis and comparison of the data from the two schools, we examine music in children's lives, music in the classroom, and musical ambitions and values, and consider how well the music curriculum serves the children in each setting.